Absolute chronology of Castelo Velho de Freixo Numão (Northern Portugal) : data and problems - Jorge, Susana Oliveira (2002)
The authors present and discuss the radiocarbon dates obtained until now for the prehistoric site of Castelo Velho de Freixo de Numão. These results, associated with stratigraphic analysis, indicate that the site was mainly occupied between 3000 and 1300 BC.